Integrasi Sains Terapan dalam Pengembangan Energi Terbarukan: Perspektif Islam pada Teknologi Plant Microbial Fuel Cell (PMFC) - Damayanti, Silva; Dwandaru, Wipsar Sunu Brams; Dewi, Imelda Zahra Tungga; Widayanti, Widayanti (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2025)
The increasing demand for sustainable energy drives innovations in environmentally friendly renewable energy technologies, one of which is the Plant Microbial Fuel Cell (PMFC), which utilizes the biochemical activity of plants to generate electricity. This study examines the potential of PMFC as an eco-friendly energy solution and its relevance to Islami teachings on environmental conservation and the sustainable use of natural resources. Experimental results show that the PMFC with Aluminium-Copper (Al-Cu) electrodes generates a maximum current of 0,396 mA and a voltage of 0,393 V, while the Aluminium-Zinc (Al-Zn) combination only produces 0,255 mA and 0,222 V. Additionally, wet soil conditions enhance the power output to 0,051 mW. This study demonstrates that PMFC can convert the chemical energy in plants into electricity without harmful emissions, aligning with Islamic principles that emphasize sustainability and the prevention of environmental damage.